SURVEILLANCE OF VECTOR PROBLEMS ON A NATIONAL BASIS AS EXAMPLIFIED BY IRAN - M.A. Faghih (Tehran University of Medical Sciences, 1972)
The significance and impact of the arthropods and other vectors, as diseases transmitting agents and human pests, on human health need not to be over emphasized. The Increasing changes of the total environment, accompanied with the climates in the ecology of vectors have made such impact a more complex and dynamic one. To meet the problems caused by these changes, a quantitative and qualitative knowledge of vector characteristics such as, presence or absence, species, densities, distribution and dispersal biting habit, infection rate, etc. are necessary. This information should be available on local, region, national and international basis. In the present paper, various aspects of such intonation system (surveillance) including network, personnel, methods etc., are reviewed in general. Examples from Iranian experiences in the cases of malaria vectors sandfiles, fleas and snails are also presented and illustrated.